Closed‐loop acoustic stimulation during an afternoon nap to modulate subsequent encoding. (19th September 2022) - Koo‐Poeggel, Ping; Neuwerk, Soé; Petersen, Eike; Grasshoff, Jan; Mölle, Matthias; Martinetz, Thomas; Marshall, Lisa
Summary: Sleep is able to contribute not only to memory consolidation, but also to post‐sleep learning. The notion exists that either synaptic downscaling or another process during sleep increase post‐sleep learning capacity. A correlation between augmentation of the sleep slow oscillation and hippocampal activation at encoding support the contribution of sleep to encoding of declarative memories. In the present study, the effect of closed‐loop acoustic stimulation during an afternoon nap on post‐sleep encoding of two verbal (word pairs, verbal learning and memory test) and non‐verbal (figural pairs) tasks and on electroencephalogram during sleep and learning were investigated in young healthy adults ( N = 16). Closed‐loop acoustic stimulation enhanced slow oscillatory and spindle activity, but did not affect encoding at the group level. Subgroup analyses and comparisons with similar studies lead us to the tentative conclusion that further parameters such as time of day and subjects' cognitive ability influenced responses to closed‐loop acoustic stimulation.